2021
DOI: 10.1016/j.jadohealth.2020.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent and Parent Perspectives on Confidentiality After Adolescent Relationship Abuse Disclosure

Abstract: This study aimed to assess adolescent and parent perspectives on parent notification after disclosure of adolescent relationship abuse (ARA) to a health care provider. Methods: A computerized survey was administered to a convenience sample of adolescents aged 14e18 years and their parents presenting to three Midwestern pediatric emergency departments. The survey assessed the acceptability of parent notification after hypothetical adolescent disclosure of different forms of ARA (i.e., physical, cyber, psycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The support of a parent or another trusted adult is especially important when an adolescent is experiencing harmful interactions such as ARA. Noteworthy in the study by Weibelhaus et al is that even though a majority of both adolescents and parents did find parental notification acceptable, adolescents who were most at risk were the least likely to find it acceptable: adolescents with prior sexual activity or prior ARA victimization or those in current dating relationships [2]. Unfortunately, although most adolescents have supportive parents, not all do and, among the parents reported in the study by Wiebelhaus et al, 35% of the participating parents had themselves experienced intimate partner violence, which might complicate their capacity to support a victimized adolescent child [2].…”
Section: Beyond Mandatory Reporting and Disclosurementioning
confidence: 96%
See 3 more Smart Citations
“…The support of a parent or another trusted adult is especially important when an adolescent is experiencing harmful interactions such as ARA. Noteworthy in the study by Weibelhaus et al is that even though a majority of both adolescents and parents did find parental notification acceptable, adolescents who were most at risk were the least likely to find it acceptable: adolescents with prior sexual activity or prior ARA victimization or those in current dating relationships [2]. Unfortunately, although most adolescents have supportive parents, not all do and, among the parents reported in the study by Wiebelhaus et al, 35% of the participating parents had themselves experienced intimate partner violence, which might complicate their capacity to support a victimized adolescent child [2].…”
Section: Beyond Mandatory Reporting and Disclosurementioning
confidence: 96%
“…Noteworthy in the study by Weibelhaus et al is that even though a majority of both adolescents and parents did find parental notification acceptable, adolescents who were most at risk were the least likely to find it acceptable: adolescents with prior sexual activity or prior ARA victimization or those in current dating relationships [2]. Unfortunately, although most adolescents have supportive parents, not all do and, among the parents reported in the study by Wiebelhaus et al, 35% of the participating parents had themselves experienced intimate partner violence, which might complicate their capacity to support a victimized adolescent child [2]. Consideration of alternatives to parental notification may be necessary to ensure that adolescents experiencing ARA victimization have the support they need to navigate a difficult situation with potentially long-term adverse effects on their health and well-being.…”
Section: Beyond Mandatory Reporting and Disclosurementioning
confidence: 96%
See 2 more Smart Citations
“…A recent study found that adolescents and parents find it acceptable for a healthcare provider to inform parents about ARA disclosure, particularly for physical ARA. 86 When discussing ARA after disclosure, healthcare providers should ask youth if there is an adult support with whom they would feel comfortable sharing their ARA experiences. This person may be a parent or another trusted adult.…”
Section: Addressing Ara In Healthcare Settingsmentioning
confidence: 99%